2022
DOI: 10.1093/ehjci/jeac242
|View full text |Cite
|
Sign up to set email alerts
|

Emerging molecular imaging targets and tools for myocardial fibrosis detection

Abstract: Myocardial fibrosis is the heart’s common healing response to injury. While initially seeking to optimize the strength of diseased tissue, fibrosis can become maladaptive, producing stiff poorly functioning and pro-arrhythmic myocardium. Different patterns of fibrosis are associated with different myocardial disease states, but the presence and quantity of fibrosis largely confer adverse prognosis. Current imaging techniques can assess the extent and pattern of myocardial scarring, but lack specificity and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 88 publications
1
13
0
4
Order By: Relevance
“…A minority of evidence has suggested that FAPI-PET imaging possesses the potential for early identification of cardiovascular fibrosis, risk stratification, and prediction of the progression of left ventricular function. 13 As expected, our finding substantiated the capability of detecting mild cardiac fibrosis through [ 68 Ga]Ga-DOTA-FAPI-04 molecular imaging. In this study, we found that both FAP protein and mRNA expression were significantly upregulated in the diabetic heart in early-and late-stage diabetes, thereby further affirming the high specificity of the [ 68 Ga]Ga-DOTA-FAPI-04 molecular probe.…”
Section: ■ Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A minority of evidence has suggested that FAPI-PET imaging possesses the potential for early identification of cardiovascular fibrosis, risk stratification, and prediction of the progression of left ventricular function. 13 As expected, our finding substantiated the capability of detecting mild cardiac fibrosis through [ 68 Ga]Ga-DOTA-FAPI-04 molecular imaging. In this study, we found that both FAP protein and mRNA expression were significantly upregulated in the diabetic heart in early-and late-stage diabetes, thereby further affirming the high specificity of the [ 68 Ga]Ga-DOTA-FAPI-04 molecular probe.…”
Section: ■ Discussionsupporting
confidence: 85%
“…Currently, the prospective utility of FAPI-PET in evaluating nononcologic pathological processes remains under active investigation. A minority of evidence has suggested that FAPI-PET imaging possesses the potential for early identification of cardiovascular fibrosis, risk stratification, and prediction of the progression of left ventricular function …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Нормальный миокард состоит из кардиомиоцитов и окружающего внеклеточного матрикса в соотношении 3:1 [1,2]. Диффузный фиброз миокарда (ФМ) встречается при различных хронических заболеваниях сердца, он возникает в результате избыточного отложения коллагеновых волокон по всему миокарду [3]. Физико-химические свойства волокон, состав коллагена и количество фиброзных отложений имеют ключевое значение во влиянии диффузного ФМ на функцию сердца и клинические исходы у пациентов с хронической сердечной недостаточностью (ХСН) [4].…”
Section: Introductionunclassified
“…ФМ является распространенной патологической реакцией на повреждение сердечной мышцы [2,3]. Первоначальное повреждение миокарда может возникнуть в результате широкого спектра стимулов, приводящих к различным формам фиброза.…”
Section: Introductionunclassified